The Correlation of Congenital Anomalies of The Kidney and Urinary Tract with Renal Function in Children - Chairunnisa; Ninik Asmaningsih Soemyarso; Risky Vitria Prasetyo (Indian Journal of Forensic Medicine & Toxicology, 2021)
Background: Congenital Anomalies Kidney and Urinary Tract (CAKUT) are the leading cause of kidneyfailure in children and cause of 30-40% end-stage renal disease with obstructive uropathy as the main cause.CAKUT obstructive type are: vesico uretric junction obstruction (VUJO), pelvic uretric junction obstruction(PUJO), posterior uretral valve (PUV) and non-obstructive type are reflux, neurogenic and hypoplasia. Theaim of this study is to describe the effect of CAKUT on renal function in child.Methods: Retrospective study from medical records of children with CAKUT at Dr. Soetomo GeneralHospital, Surabaya, Indonesia from January 2013 - March 2018. The characteristic of sex, age range, type ofCAKUT and glomerulus filtration (GFR) value were recorded from medical record. Data processing usingdescriptive analysis with SPSS.Result: A total of 94 Children on CAKUT abnormalities, both boys and girl’s presentation equal 50%.Median age 3.0 (minimum-maximum 1.0-15.0) year. The most common CAKUT type in male were VUJO17 (36.2%) and in female neurogenic type 19 (40.4%). Median initial glomerular filtration rate 2.7 ml/min/1.73 m2. Analysis of correlation between CAKUT and renal function p=0.072 (R2=0,03). From 94children of CAKUT, only 12 (12.8%) patients have undergo surgical intervention.Conclusion: CAKUT with dominant obstructive type was more common in male and non-obstructive typein female pediatric patient. There was no significance correlation of GFR between obstructive and nonobstructive type.